Iran's Nuclear Future Critical U.S. Policy Choices - Davis, Lynn E. (RAND Corporation, 2011)
As Iran's nuclear program evolves, U.S. decisionmakers will confront a series of critical policy choices involving complex considerations and policy trade-offs. These policy choices could involve dissuading Iran from developing nuclear weapons; deterring Iran from using its nuclear weapons, if it were to acquire them; and reassuring U.S. regional partners. The U.S. Air Force will need to prepare to carry out whatever policies are chosen.